Muscle thickness of serratus anterior muscle during performing wall push-up plus and standard push-up plus using ultrasound imaging - Nipaporn Wannaprom; Kamonjutha Onket; Jakkapop Puachaikul; Sureeporn Uthaikhup (Journal of Associated Medical Sciences, 2017)
Background: Serratus anterior exercise is an important rehabilitation program in clinical practices. Different positions may affect muscle activity. However, there has no report investigating the thickness of serratus anterior during contraction in different positions.